Transforming public services - Moloney David; Dwyer Rowena; Glavey Sarah; Sellars Dermot (Administration)
The public service works to provide frontline and vital services to meet the needs of the people of Ireland. Working on behalf of the government in a diverse range of organisations, public servants play an established role in the economic and social life of this country. The public service has grown and evolved to take advantage of opportunities, address new challenges, and meet the changing needs and expectations of the people of Ireland. Since 2011, the Department of Public Expenditure, NDP Delivery and Reform, has led a dedicated programme for reform and transformation, used its role and functions to enhance governance, build capacity and delivery effectively, working with the full range of public service bodies to build a more unified and agile public service. In 2023, the department published Better Public Services, a strategy that lays out the current framework and programme of transformation up to 2030, which is delivering tangible outcomes in improved public services, living standards and infrastructure in Ireland.